FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI - Vera Marcelina; Samin Samin; Kornel Sitanggang (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2019)
This research is using quantitative study aimed to see whether there are influence of dividend policy, leverage and profitability to firm value. The population used in this study is a manufacturer firm listed on the Indonesia Stock Exchange (BEI) in the period 2014-2017. By using purposive sampling method, it is obtained as many as 53 firm as the study sample. The method of analysis used in this study is multiple linier regression with a significant level of 0.05 (5%). In this research also include the classical assumption that normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. The results of these test indicate that (1) there is significant influence of dividend policy to firm value. (2) there is significant influence of leverage to firm value and (3) there is no significant influence of profitability to firm value. Keywords : dividend policy, leverage, profitability, firm value.